ANESTHESIA IN SURGERIES ON THE FOOT AND ANKLE (REVIEW) - N. A. Koryshkov; S. V. Larionov; N. A. Murashova; K. A. Sobolev (Travmatologiâ i Ortopediâ Rossii, 2012)
Among the various anesthetic options the combination of spinal anesthesia with the implementation of regional nerve blocks of the lower extremity and local anaesthesia of area of the wound with long-acting local anesthetics is more interesting. However the recommendations for the choice of postoperative analgesia of the foot do not exist, inspite of the pain syndrome. The prospects for wider use of regional blocks include the use of electrical stimulator in conjunction with ultrasound identification of the nerve trunks, the use of infusion pumps and catheter techniques blockades.